Mechanisms of state and private partnership on efficient development of self-employment in Kazakhstan (Journal of Economic Research & Business Administration, 2017)
Aim of the project is to study functioning mechanisms of conglomerate of various groups of self-employed population (urban and rural) in the view of regions and spheres for comparison of indicators of development of RK socio-economic system with worldwide tendencies in evaluation of self-employed.Methodology. Methodological approach is based on common scientific systemic method, empirical study and methods of quantitative and qualitative analysis, econometrics modeling of complex dynamic systems , theory and practice of public and private management, contemporary economic theories and concepts. Applicable outcomes of research. Based on results of conducted study there would be conclusions and recommendations on self-employment model creation with the aim of formation of flexible labour market in the Republic of Kazakhstan. Results of scientific research help to build new strategies of flexible labour market and employment policy of population, that would support process of development efficient self-employment in small and medium business.